Drivers of Change for Grassland and Forage Systems: A Case Study of China - Zhang, Yingjun; Zhang, L.Z.; Wang, M.L.; Li, X.L.; Yang, Q.C.; Hanson, Jean; Jorge, M.A.B. (International Livestock Research Institute, 2013)
Grassland and forage systems have changed dramatically across the world. This paper describes some of the key drivers of change of grassland and forage systems using examples from China as a case study. The key drivers of change for grassland and forage systems include political, economic, social, technical and environmental factors and their impact on changes in grasslands ecosystems in China is discussed. There are interactions among the drivers and their impact is similar in many developing countries.